Adjuvant S-1 compared with observation in resected biliary tract cancer (JCOG1202, ASCOT): a multicentre, open-label, randomised, controlled, phase 3 trial. Issue 10372 (21st January 2023) - Nakachi, Kohei; Ikeda, Masafumi; Konishi, Masaru; Nomura, Shogo; Katayama, Hiroshi; Kataoka, Tomoko; Todaka, Akiko; Yanagimoto, Hiroaki; Morinaga, Soichiro; Kobayashi, Shogo; Shimada, Kazuaki; Takahashi, Yu; et al.
Summary: Background: S-1 has shown promising efficacy with a mild toxicity profile in patients with advanced biliary tract cancer. The aim of this study was to evaluate whether adjuvant S-1 improved overall survival compared with observation for resected biliary tract cancer. Methods: This open-label, multicentre, randomised phase 3 trial was conducted in 38 Japanese hospitals. Patients aged 20–80 years who had histologically confirmed extrahepatic cholangiocarcinoma, gallbladder carcinoma, ampullary carcinoma, or intrahepatic cholangiocarcinoma in a resected specimen and had undergone no local residual tumour resection or microscopic residual tumour resection were randomly assigned (1:1) to undergo observation or to receive S-1 (ie, 40 mg, 50 mg, or 60 mg according to body surface area, orally administered twice daily for 4 weeks, followed by 2 weeks of rest for four cycles). Randomisation was performed by the minimisation method, using institution, primary tumour site, and lymph node metastasis as adjustment factors. The primary endpoint was overall survival and was assessed for all randomly assigned patients on an intention-to-treat basis. Safety was assessed in all eligible patients. For the S-1 group, all patients who began the protocol treatment were eligible for a safety assessment. This trial is registered with the University hospital Medical Information Network Clinical Trials Registry (UMIN000011688). Findings: Between Sept 9, 2013, and June 22, 2018, 440 patients were enrolled (observation group n=222 and S-1 group n=218). The data cutoff date was June 23, 2021. Median duration of follow-up was 45·4 months. In the primary analysis, the 3-year overall survival was 67·6% (95% CI 61·0–73·3%) in the observation group compared with 77·1% (70·9–82·1%) in the S-1 group (adjusted hazard ratio [HR] 0·69, 95% CI 0·51–0·94; one-sided p=0·0080). The 3-year relapse-free survival was 50·9% (95% CI 44·1–57·2%) in the observation group compared with 62·4% (55·6–68·4%) in the S-1 group (HR 0·80, 95% CI 0·61–1·04; two-sided p=0·088). The main grade 3–4 adverse events in the S-1 group were decreased neutrophil count (29 [14%]) and biliary tract infection (15 [7%]). Interpretation: Although long-term clinical benefit would be needed for a definitive conclusion, a significant improvement in survival suggested adjuvant S-1 could be considered a standard of care for resected biliary tract cancer in Asian patients. Funding: The National Cancer Center Research and the Ministry of Health, Labour, and Welfare of Japan.